School geography course ecologization in the 90s - Оржаховська, Анастасія Геннадіївна (Pedagogy of Higher and Secondary Education, 2013)
Orzhahovska A. G. School geography course ecologization in the 90s. The article deals with the concept «ecologization of geography», examines the role of pedagogical media in environmental education process, gives examples of environmental knowledge implementation into different educational institutions and students’ involving into environmental problems solving.